Faktor yang Mempengaruhi Produksi Usahatani Jagung di Desa Lorotolus Kecamatan Wewiku Kabupaten Malaka - Adrianus Seran Kolik; Simon Juan Kune (Fakultas Pertanian, Universitas Timor, 2019)
This study aims to describe maize farming and analyzing the factors that affect maize production in Lorotolus Village, Wewiku District, Malaka Regency. The method used is descriptive qualitative analysis and Cobb-Douglas analysis using multiple linear regression. This research was conducted from February to July 2018 in Lorotolus Village. The results of the analysis showed that the factors significantly affected maize production in Lorotulus were the number of seeds and the number of labors. Other independent variables in this study did not significantly affect maize production in Lorotulus Village.